Association of maternal diabetes and child asthma1. Issue 6 (4th September 2012) - Azad, Meghan B.; Becker, Allan B.; Kozyrskyj, Anita L.
Abstract Background Perinatal programming is an emerging theory for the fetal origins of chronic disease. Maternal asthma and environmental tobacco smoke (ETS) are two of the best‐known triggers for the perinatal programming of asthma, while the potential role of maternal diabetes has not been widely studied. Objective To determine if maternal diabetes is associated with child asthma, and if so, whether it modifies the effects of ETS exposure and maternal asthma. Methods We studied 3, 574 Canadian children, aged 7–8 years, enrolled in a population‐based birth cohort. Standardized questionnaires were completed by the children's parents, and data were analyzed by multivariable logistic regression. Results Asthma was reported in 442 children (12.4%). Compared to those without asthma, asthmatic children were more likely to have mothers (P = 0.003), but not fathers (P = 0.89), with diabetes. Among children without maternal history of diabetes, the likelihood of child asthma was 1.4‐fold higher in those exposed to ETS (adjusted odds ratio, 1.40; 95% confidence interval, 1.13–1.73), and 3.6‐fold higher in those with maternal asthma (3.59; 2.71–4.76). Among children born to diabetic mothers, these risks were amplified to 5.7‐fold (5.68; 1.18–27.37) and 11.3‐fold (11.30; 2.26–56.38), respectively. In the absence of maternal asthma or ETS, maternal diabetes was not associated with child asthma (0.65, 0.16–2.56). Conclusion Our findings suggest that maternal diabetes may contribute to the perinatal programming of child asthma by amplifying the detrimental effects of ETS exposure and maternal asthma. Pediatr Pulmonol. 2013; 48:545–552. © 2012 Wiley Periodicals, Inc.